Catalytic evaluation of Pd-promoted Ni-Co/Al2O3 catalyst for glycerol dry reforming: Assessing hydrogen-rich syngas production, kinetics and mechanisms - Nor Shafiqah, Mohd Nasir; Mohamed, Hassan; Panpranot, Joongjai; Sumaiya Zainal, Zainal Abidin (Elsevier Ltd, 2024)
The Pd-promoted Ni-Co bimetallic catalysts were prepared using ultrasonic-assisted impregnation, and their performance was subsequently assessed in a fixed-bed reactor. The catalyst's performance was evaluated in glycerol dry reforming (GDR) over a range of temperatures, from 873 K to 1173 K and reactant partial pressures ranging from 10 kPa to 40 kPa. The results indicated that as the temperature was raised from 873 K to 1073 K, there was a noticeable rise in both reactant conversion and product yield. However, beyond 1173 K, catalytic performance declined due to glycerol thermal cracking and sintering of the support at high temperatures, resulting in increased carbon formation. The presence of excessive CO2 was found to suppress glycerol adsorption on the catalyst surface, causing a decline in catalytic activity with a CO2 partial pressure of more than 20 kPa, regardless of reaction temperature. Additionally, excess CO2 were found to enhance the side reaction, particularly reverse water-gas shift (RWGS) that related to produce intermediate H2O. Similarly, the glycerol partial pressure was found to impact catalytic performance, with a decrease in performance beyond 20 kPa due to competing reactants between glycerol and CO2. According to the Langmuir-Hinshelwood kinetic mechanism, a dual molecular adsorption site for glycerol and CO2 was appropriate for this GDR reaction, with an associated activation energy of 47.3 kJ mol−1. The GDR reaction was identified as a kinetically controlled process due to its high activation energy, more than 25 kJ mol−1. The plausible mechanism of GDR over Pd-Ni-Co/Al2O3 occurred through the dissociative-type of adsorption of on active metallic sites of the catalysts for both reactant (glycerol and CO2). This was further facilitated by the bifunctional mechanisms based on H2 generated from dissociative adsorption involving both catalyst's basic sites and metallic active sites. This was ascribed to the highly dispersed and strong interaction between metal-support in Pd-promoted Ni-Co bimetallic catalysts.